MENINGKATKAN KEBERANIAN MENGUNGKAPKAN PENDAPAT DAN MENGAMBIL KEPUTUSAN MATERI KERJASAMA DAN PERJANJIAN INTERNASIONAL YANG BERMANFAAT BAGI INDONESIA PADA MATA PELAJARAN PKN MELALUI MODEL MORAL REASONING DI KELAS XI IPS2 SMA NEGERI 10 BANJARMASIN - Norma Megawati (Jurnal Pendidikan Kewarganegaraan, 2014)
NormaMegawati, 2014CourageRevealOpinionsImproveDecision-MakingMaterialsAndCooperationandInternationalAgreementsUsefulFor IndonesiaInCivicsLesson ImplementationThrough theModelMoralReasoningInClassXIIPS2SMA Negeri10Banjarmasin. Supervisor(I) H.Sarbaini(II) Hj. Siti Fatimah. Civicslearningprocessinclass XI IPS2SMANegeri 10Banjarmasintendnotachieveexpected. Low activityconditionseffect on the qualityof student learningin the classroom. Learning thattakes placeina classof studentswho are goodlooksalonewere activewhenexpressing an opinion, this situationresults instudentswhoare still notfamiliar with the materialdescribedteachersfeelembarrassedtoask questions andexpress their opinionsbecause they feelembarrassedandnotappreciated. Lack ofdemocraticattitudesof studentscan be seenfromthe lowmotivation ofdemocracystudentin group discussion activities. Studentspay less attention tothe teacherexplainsandengrossed himself, only a few studentsare able tocapture theteacherexplainedthe material. This resulted inpoorlearning outcomes. The purpose ofthe studyistopromote student participation inthelearningCivicsexpressionby usinga modelof moralreasoninginclassXISMAIPS210Banjarmasin.Data collection techniquesused inclassroom action research(CAR) is theobservation, documentationandteststudyconductedthroughseveralcycles, thefirst cycleandsecond cycle.The results ofthis study indicate(1) Learningteacherin implementing thelearning modelof moralreasoningtakes placesmoothly. In the first cycleof learningteacherprettygoodin qualifyingandin the second cyclehas increased verywellwithgoodqualifications. (2) activityincreasedverygoodstudentswithgoodqualifications. (3) The processof learningto applymoralreasoningmodelscanincrease the activity ofstudents inexpressingtheiropinions andmake decisions.Based on these results, it is suggested thattheschoolshould beable to putthe teacherin accordancewith thequotaof students, in order to getquality graduatesnotonlymenonjokanvaluebut alsothe valueof cognitiveaffectiveandpsychomotor. Civicsteacher, shouldshould beheldin therenewal ofthe learningprocessbetterandbe able toapply themodel ofmoralreasoningas analternative tolearningin order tobe able torunwith thegoalof learningoptimal. Keywords: express opinions, make decisions, dilemmastories